Hippo Signaling Pathway in Colorectal Cancer: Modulation by Various Signals and Therapeutic Potential - Somayeh Mohammadpour; Amir Torshizi Esfahani; SeyedKasra Sarpash; Fatemeh Vakili; Nikta Zafarjafarzadeh; Amirhesam Mashaollahi; Ali Pardakhtchi; Ehsan Nazemalhosseini-Mojarad (Analytical Cellular Pathology)
Colorectal cancer (CRC) stands as a significant global health issue, marked by elevated occurrence and mortality statistics. Despite the availability of various treatments, including chemotherapy, radiotherapy, and targeted therapy, CRC cells often exhibit resistance to these interventions. As a result, it is imperative to identify the disease at an earlier stage and enhance the response to treatment by acquiring a deeper comprehension of the processes driving tumor formation, aggressiveness, metastasis, and resistance to therapy. The Hippo pathway plays a critical role in facilitating the initiation of tumorigenesis and frequently experiences disruption within CRC because of genetic mutations and modified expression in its fundamental constituents. Targeting upstream regulators or core Hippo pathway components may provide innovative therapeutic strategies for modulating Hippo signaling dysfunction in CRC. To advance novel therapeutic techniques for CRC, it is imperative to grasp the involvement of the Hippo pathway in CRC and its interaction with alternate signaling pathways, noncoding RNAs, gut microbiota, and the immune microenvironment. This review seeks to illuminate the function and control of the Hippo pathway in CRC, ultimately aiming to unearth innovative therapeutic methodologies for addressing this ailment.